MSMEs as a Driving Motor for Decent Work Towards a Sustainable Indonesian Economy - Fhaisa Rayya Zuriani Haryono; Angelika Mariana Sihombing; Indah Prabawati; Firre An Suprapto (Income Journal Of Economics Development, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy because they are able to encourage entrepreneurship, expand job opportunities, and increase productivity. In the labor market, MSMEs are the main source of employment for groups that have limited access to formal employment. This study uses a literature review method with a qualitative descriptive approach to analyze the role of MSMEs as a driver of decent jobs towards a sustainable Indonesian economy. The results of the study show that MSMEs contribute significantly to labor absorption and inclusive economic growth, especially for groups that have limited access to the formal sector. However, the quality of the work produced still faces various challenges, such as low wages, lack of social protection, and suboptimal working conditions. Therefore, policy support, human resource capacity building, and digital transformation are needed to strengthen the role of MSMEs in creating decent jobs and supporting Indonesia's sustainable economy.